A COMPARATIVE STUDY OF GAME-BASED LEARNING AND POWER POINT-MULTIMEDIA INSTRUCTION IN TEACHING ENGLISH SPEAKING SKILLS - Hadiwinarto, Eucharisha Ilonna Gitasari; Susanto, Allvian Ika Fiki (Jurnal Bahasa Lingua Scientia, 2025)
Various teaching methodologies have been applied in teaching English speaking skills throughout Indonesia, among them are Game Based Learning (GBL) and Power point-Multimedia Based Learning (PMBL). Therefore, in this paper, the author has explored the effectiveness of both learning methods in enhancing the English-speaking skills of fourteen seven graders in Mondial Junior High School. The research was conducted by employing comparative quantitative research, with the design of post-test only design. The data collection was taken by the help of a modified IELTS speaking test method, and the data was examined by an independent sample t-test. The data analyst shows that there were no significant differences, which means that the two learning methods were proven to be both effective for the seven graders in Mondial Junior High School. Other than that, the speaking test results shows an unique pattern outcome comparing both learning treatments.